Acta Mechanica - Irschik, Hans.; Weng, George J.; Ostoja-Starzewski, Martin; Krommer, Michael; Marchioli, Christian; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer.)
Since 1965, the international journal Acta Mechanica has been among the leading journals in the field of theoretical and applied mechanics. In addition to the fields of solid and fluid mechanics, such as elasticity, plasticity, vibrations and control, structures, multi-body dynamics, hydrodynamics, gasdynamics and multiphase flows, it also gives special attention to areas such as Non-Newtonian fluid dynamics, micro- and nanomechanics of fluids and solids, smart materials and structures, biomechanics of solids and fluids, stochastic mechanics, and novel issues at the interface of mechanics and materials. The journal further publishes papers in such related fields as rheology, thermodynamics, and electromagnetic interactions with fluids and solids. Acta Mechanica emphasizes originality in all aspects of theoretical, experimental, and computational mechanics that are of lasting value and of current interest. Acta Mechanica will also publish special issues and editor-invited Reviews and Perspectives.
Keywords: Continuum physics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mechanics; Mechanics, Applied; Vibration; Dynamical systems; Dynamics; Fluid mechanics; Theoretical and Applied Mechanics; Classical and Continuum Physics; Solid Mechanics; Engineering Fluid Dynamics; Vibration, Dynamical Systems, Control; Engineering Thermodynamics, Heat and Mass Transfer